Assessment of transmission loss allocation algorithms in deregulated power system - Hassan, Mohammad Yusri (2012)
In most of the competitive electric pool markets worldwide, transmission losses are not included in transmission use of system charge. Thus, the charge levied to transmission users is based solely on DC power flow regardless the amount of power losses the users cause in the transmission grid. This allocation of transmission losses is significant for the transmission owner as well as it could help reducing location al charge for the user creating counter flow to relieve the transmission network. This paper focuses on the analysis of the performance of different loss allocation methods for pool-based electricity market. The study is based on: pro-rata; proportional sharing; Z-bus; modified nodal equation; current adjustment factors, incremental loss (ITL) and Loss Utilization Factor (LUF) method. Case studies based on a simple 5-bus and IEEE 14-bus systems are used to show the capability of different loss allocation algorithms in allocating losses to the transmission users.